Biosimilar insulins in international and domestic practice of pharmacist - I. O. Vlasenko; I. V. Nizhenkovska (The State Expert Center of the Ministry of Health of Ukraine, 2022)
In Ukraine, people with diabetes receive insulin, including insulin biosimilars in pharmacies, so pharmacists should increase their knowledge about biosimilar because they become more available in the coming years. The aim of the work was to summarize current information on insulin biosimilars. Research materials ‒ regulatory database information and scientific publications on biosimilars. Content analysis, bibliosemantic, analytical, generalizing analyzes were used. The terminology related to reproducible biological drugs (biosimilars) is difference and it depend on the regulatory agency or the country that controls the approve of drugs. Insulin was the first biopharmaceutical drug which was developed. For approving biosimilars, it is necessary to establish similarity with the reference drug in terms of safety, purity and efficacy. Regulatory of biosimilars and requirements for demonstration the biosimilarity are specified in regulatory of the EMA and WHO. The regulatory of the approving of biosimilar in Ukraine is harmonized with European regulatory. The rules on interchangeability are not determined by all regulatory agency. The International Diabetes Federation emphasizes the role of the pharmacist, stating that they should be well informed about the forms of insulin, includes biosimilars. In Ukraine, pharmacists must dispense insulin, including biosimilars, exactly in accordance to the prescription in which the trade name of insulin (or biosimilars) is indicated. Insulin biosimilars can be an alternative to original insulins that have lost patent protection by increasing the availability of drugs, which can lead to increased market competition and access insulin for patients. Based on the analysis of current information on biosimilars, generalizations about their terminology, aspects of manufecture, regulatory, interchangeability, prospects in the treatment of diabetes and their replacement of referens insulins are presented. The potential impact of biosimilar insulins to patients and the health care system was determinated. The importance of awareness of these drugs by pharmacists as part of the diabetic team are highlighted.